2007
DOI: 10.1016/j.febslet.2007.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Squalene cyclase and oxidosqualene cyclase from a fern

Abstract: Ferns are the most primitive vascular plants. The phytosterols of ferns are the same as those of higher plants, but they produce characteristic triterpenes. The most distinct feature is the lack of oxygen functionality at C-3, suggesting that the triterpenes of ferns may be biosynthesized by direct cyclization of squalene. To obtain some insights into the molecular bases for the biosynthesis of triterpenes in ferns, we cloned ACX, an oxidosqualene cyclase homologue, encoding a cycloartenol synthase (CAS) and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…Some of these structures are identical to bacterial hopanoids. For example, several members of the Polypodiales (polypod) order of ferns encode an SHC enzyme 24 that seems to exclusively produce the C 30 hopanoid diplopterol in vitro 27 . It is likely that these ferns acquired shc by horizontal transfer from bacteria 28 .…”
Section: Hopanoid Structure and Biosynthesismentioning
confidence: 99%
“…Some of these structures are identical to bacterial hopanoids. For example, several members of the Polypodiales (polypod) order of ferns encode an SHC enzyme 24 that seems to exclusively produce the C 30 hopanoid diplopterol in vitro 27 . It is likely that these ferns acquired shc by horizontal transfer from bacteria 28 .…”
Section: Hopanoid Structure and Biosynthesismentioning
confidence: 99%
“…Changes in expression in a BY-2 control line (transformed with the empty vector, pER8.1) are also shown regulatory details are still obscure. In this contribution, we focused our attention on one key enzyme in the pathway, CAS [14,15,23,[43][44][45], and on its regulatory role in the well-established tobacco BY-2 cell system [33,34]. Admittedly, observations on cell cultures may not always hold true for intact plants.…”
Section: Different Approaches To Analysis Of Phytosterol Biosynthesismentioning
confidence: 98%
“…They belong to the OSC family and catalyze the transformation of oxidosqualene of chair-boat-chairboat and reorganize the cytoskeleton to produce cycloartenol (Wang et al 2010) and lanosterol. The authors cloned and identified CAS from different plants including Arabidopsis thaliana (Babiychuk et al 2008), fern (Shinozaki et al 2008), Kalanchoe daigremontiana (Wang et al 2010) and Huperzia carinata (Niu et al 2012). Cloning was necessary because of the low concentrations found in plants; however, the community has failed to appreciate the distribution of LAS catalyses in the production of ergosterol and cholesterol.…”
Section: Phytochem Revmentioning
confidence: 98%